From Convergence to Divergence: Portuguese Economic Growth, 1527-1850 - Nuno Palma; Jaime Reis (European Historical Economics Society (EHES), 2018)
We construct the first time-series for Portugal's per capita GDP for 1527-1850, drawing on a new database. Starting in the early 1630s there was a highly persistent upward trend which accelerated after 1710 and peaked 40 years later. At that point, per capita income was high by European standards, though behind the most advanced Western European economies. But as the second half of the eighteenth century unfolded, a phase of economic decline was initiated. This continued into the nineteenth century, and by 1850 per capita incomes were not different from what they had been in the early 1530s.
Keywords: N13; O52; 330; Early Modern Portugal; Historical National Accounts; Standards of Living Debate; the Little Divergence; Malthusian Model